Evaluation of Generation-wise Performance of Hybrid Layers under Reciprocal Recurrent Selection - Ramesh Kumar; S. Kalra; S. Singh; B.Parkash (Journal of Livestock Biodiversity, 2025)
In the present study generation wise performance of hybrid layers has been evaluated under reciprocal recurrent selection with the aim to devise suitable breeding strategy. Performance data spread over 9 generations from 1994 to 2003 were utilized for the study. The average egg number upto 40 weeks of age ranged from 55.28±0.63 to 81.48±0.75 and 57.02±1.04 to 81.25±0.71 in purebreds and crossbreds, respectively. The egg production declined during fourth and sixth generation. The average egg weight ranged from 49.15±0.18 g to 53.70±0.18 g in purebreds and 48.06±0.32 g to 53.21±0.22 g in crossbreds over the generations. Heritability estimates for egg number and egg weight in purebred was 0.255±0.054 and 0.286±0.060 and 0.324±0.090 and 0.369±0.061, respectively in crossbreds. In general crossbreds were slightly superior to the purebreds for most of the performance traits.